2023
DOI: 10.1039/d3nr03839d
|View full text |Cite
|
Sign up to set email alerts
|

Self-templated flower-like NiCoZn-carbonate hydroxide hollow nanospheres for asymmetric supercapacitors with high performance

Rongrong Liu,
Xin Gao,
Yanqiu Xie
et al.

Abstract: Flower-like NiCoZn-carbonate hydroxide hollow nanospheres were prepared and used as the positive electrode in a supercapacitor having superior cycling stability of 99.9% after 15 000 cycles at 10 A g−l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…36 Recently, modifications on NiCo-and other LDHs have been performed to further enhance the supercapacitor performance. [39][40][41] It is revealed that the best supercapacitor performance in NiCo-CH is primarily due to the optimized morphology and Ni : Co ratio. 42 Recently, Bhatt et al reported that the Ni : Co ratio leads to a change in the electronic properties of the material and thus the electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…36 Recently, modifications on NiCo-and other LDHs have been performed to further enhance the supercapacitor performance. [39][40][41] It is revealed that the best supercapacitor performance in NiCo-CH is primarily due to the optimized morphology and Ni : Co ratio. 42 Recently, Bhatt et al reported that the Ni : Co ratio leads to a change in the electronic properties of the material and thus the electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%